SIMULTANEOUS DETERMINATION AND ANTI-INFLAMMATORY EFFECTS OF TRADITIONAL HERBAL MEDICINE, MAHWANG-TANG - Seo, Chang-Seob; Yoo, Sae-Rom; Jeong, Soo-Jin; Ha, Hyekyung (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Mahwang-tang (MT) is a traditional Korean medicine consisting of six medicinal herbs and is used totreat the influenza-like diseases.Materials and Methods: We performed the simultaneous analysis of nine bioactive components in an MT sampleusing a high-performance liquid chromatography–diode array detector (HPLC–DAD) analysis. In addition, the MTsample was investigated the inhibitory effects against lipopolysaccharide (LPS)-stimulated RAW 264.7 cells.Results: Recovery of the nine marker compounds was 98.24–102.05% and relative standard deviations of intra-day andinter-day precisions of this method were 0.05–1.92% and 0.02–1.64%, respectively. Amounts of the nine bioactivecompounds in the MT samples were 0.24–24.86 mg/g. To determine the biological activity of MT, its effects on theinflammatory reaction in LPS-treated RAW 264.7 macrophages were tested. The results suggest that MT possessesanti-inflammatory activity via suppression of the nitric oxide/prostaglandin E2 pathway.Conclusion: The established analytical method by HPLC–DAD is expected to help the quality control of MT samplesor related herbal prescriptions. Our data also suggest that MT may be a potential therapeutic candidate for variousinflammatory diseases.